PARAMetric identification of dynamic objects via phase-frequency characteristicS - A. V. Markov; V. I. Simankov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The method of dynamic objects parametric identification via its phase-frequency characteristics is described. A comparison and selection of the first-order numeric methods for a solution of the least squares task is done. A parametric identification of the real plant via its empiric characteristics is implemented. A comparison of the developed method and method «procest», which is realized in the CAD MATLAB, is done.